Diagnostic accuracy of magnetic resonance imaging (MRI) prostate imaging reporting and data system (PI‐RADS) scoring in a transperineal prostate biopsy setting. (22nd October 2014) - Grey, Alistair D.R.; Chana, Manik S.; Popert, Rick; Wolfe, Konrad; Liyanage, Sidath H.; Acher, Peter L.
<x xml:space="preserve">Abstract</x> Objectives To determine the sensitivity and specificity of multiparametric magnetic resonance imaging (mpMRI) for significant prostate cancer with transperineal sector biopsy (TPSB) as the reference standard. Patients and Methods The study included consecutive patients who presented for TPSB between July 2012 and November 2013 after mpMRI (T2‐ and diffusion‐weighted images, 1.5 Tesla scanner, 8‐channel body coil). A specialist uro‐radiologist, blinded to clinical details, assigned qualitative prostate imaging reporting and data system (PI‐RADS) scores on a Likert‐type scale, denoting the likelihood of significant prostate cancer as follows: 1, highly unlikely; 3, equivocal; and 5, highly likely. TPSBs sampled 24–40 cores (depending on prostate size) per patient. Significant prostate cancer was defined as the presence of Gleason pattern 4 or cancer core length ≥6 mm. Results A total of 201 patients were included in the analysis. Indications were: a previous negative transrectal biopsy with continued suspicion of prostate cancer (n = 103); primary biopsy (n = 83); and active surveillance (n = 15). Patients' mean (±sd) age, prostate‐specific antigen and prostate volumes were 65 (±7) years, 12.8 (±12.4) ng/mL and 62 (±36) mL, respectively. Overall, biopsies were benign, clinically insignificant and clinically significant in 124 (62%), 20 (10%) and 57 (28%) patients, respectively. Two of 88 men with a PI‐RADS score of 1 or 2 had significant prostate cancer, giving a sensitivity of 97% (95% confidence interval [CI] 87–99) and a specificity of 60% (95% CI 51–68) at this threshold. Receiver–operator curve analysis gave an area under the curve of 0.89 (95% CI 0.82–0.92). The negative predictive value of a PI‐RADS score of ≤2 for clinically significant prostate cancer was 97.7% Conclusion We found that PI‐RADS scoring performs well as a predictor for biopsy outcome and could be used in the decision‐making process for prostate biopsy.